Analysis of Learning Difficulties of ABK Students And Solutions in Learning - Siregar, Annisa Syafitri; Daulay, Nikmatul Khoiriyah (International Journal of Students Education, 2023)
A child with special needs is a child who needs special treatment because of growth disorders and abnormalities that the child has. Children with special needs also have characteristics such as: 1) even though they are already adults, they have difficulty communicating, experience speech impediments and use inappropriate word choices, 2) experience disturbances in one or more basic psychological abilities, 3) experience physical differences and medical from other children, 3) Has a rebellious attitude, 4) Is easily angry, likes to be alone, depressed and easily annoyed with other people, 4) Generally finds it difficult to write and read, 5) Difficult to digest logic, 6) Will feel anxious and anxious if his habits change or are disturbed, 7) Likes to imitate but doesn’t understand what he is imitating, 8) Talks non-stop, 9) Acts nervous by adopting strange habits, 10) Has an envious attitude, 11) Is sensitive. Inclusive education is education that views all individuals, including children with special needs (ABK), as having the same right to obtain quality and relevant education.The problem of learning success for students with special needs (ABK) has become a very important concern in the context of inclusive education. This research aims to determine the learning difficulties of ABK students and their solutions in learning. This research uses a literature review or literacy study method with data sources from websites, books, previous research and journals. The results of this research show that many ABK students face learning difficulties, especially in physical problems, in communication, attention, emotional control, and adaptation to lesson material. To overcome the various problems of ABK students in the world of education, the participation of parents, the role of schools and teachers, and the role of the community are very necessary.